Karakterisasi dan Formulasi Uji Sitotoksik Nanopartikel PLGA-pcDNA 3.1-SB3-HBcAg dari Gel Retardation Assay sebagai Delivery Agent Kandidat Vaksin DNA Hepatitis B - Lalu Unsunnidhal; Raudatul Jannah; Fihiruddin; Nurul Inayati; Agus Supinganto (LPPM STIKES Guna Bangsa, 2023)
Indonesia is one of the countries that has the highest prevalence of HBsAg (hepatitis B disease), ranging from 2.5% to 10%, with the highest levels reported in North Sulawesi with 33.0%, Papua with 12.8%, and Pontianak with 9.1%. Strategies to overcome these obstacles include using formulations such as nanoparticles, which are formed by coacervation between polymers and DNA. This study showed that the results of the physicochemical characterization of PLGA-pcDNA 3.1-SB3-HBcAg showed a polydispersity index value of 0.246, a particle size of 925 nm, and a zeta potential value of 2.31 mV. PLGA managed to protect PLGA-pcDNA 3.1-SB3-HBcAg from enzymatic degradation, and the viability percentage of the PLGA-pcDNA 3.1-SB3-HBcAg cytotoxicity test was 98.03%, so that PLGA has good potential as a delivery system for PLGA -pcDNA 3.1-SB3- HBcAg.